T‐cell clones in human trichinellosis: Evidence for a mixed Th1/Th2 response. (March 2017) - Della Bella, C.; Benagiano, M.; De Gennaro, M.; Gomez‐Morales, M. A.; Ludovisi, A.; D'Elios, S.; Luchi, S.; Pozio, E.; D'Elios, M. M.; Bruschi, F.
Summary: In humans, studies on the cellular immune response against Trichinella are scarce. Aim of this study was to characterize the cytokine profile of T cells specific for Trichinella britovi in trichinellosis patients. Peripheral blood mononuclear cells (PBMC) were obtained from five patients involved in a trichinellosis outbreak caused by T. britovi, which occurred in 2013 in Tuscany (Italy). All the patients resulted positive for Trichinella ‐specific IgG, IgE and presented eosinophilia. T cells were investigated for their proliferation to excretory/secretory antigens from Trichinella spiralis muscle larvae (TsES) and for their cytokine profile. A total of 284 CD4+ and 42 CD8+ T‐cell clones were obtained from the TsES‐specific T‐cell lines from PBMC. All T‐cell clones proliferated in response to mitogen. Of the 284 CD4+ T‐cell clones generated from TsES‐specific T‐cell lines, 135 (47%) proliferated significantly to TsES; 26% CD8+ T‐cell clones showed proliferation to TsES. In the series of the 135 TsES‐specific CD4+ clones, 51% expressed a Th2 profile, 30% a Th0 and 19% Th1. In the series of the 11 TsES‐specific CD8+ T‐cell clones, 18% were Tc2, 45% Tc0 and 36% Tc1. In human trichinellosis, the cellular immune response is, during the chronic phase, mixed Th1/Th2.